X-ray and UV-Vis-NIR absorption spectroscopy studies of the Cu(I) and Cu(II) coordination environments in mixed alkali-lime-silicate glasses - Grund Bäck, Lina; Ali, Sharafat; Karlsson, Stefan; Wondraczek, Lothar; Jonson, Bo (Journal of Non-Crystalline Solids: X, 2019)
The local structures of Cu(I) and Cu(II) in (20-x)Na2O-xK2O-10CaO-70SiO2 glasses with a copper content of 0.4 mol% have been investigated by Cu K-edge extended X-ray absorption fine structure (EXAFS) and X-ray absorption near edge structure (XANES). Complementary data for Cu(II) was derived using UV–Vis-NIR spectroscopy. Indication for mainly linear two-fold coordination of the Cu+ ion was found by both EXAFS and XANES, but other coordination between Cu+ and O2– cannot be excluded. The Cu(I)&O bond lengths were found to be 1.79–1.83 ± 0.02 Å. EXAFS results showed that Cu(II) was mostly present in a Jahn-Teller distorted environment with oxygen, an octahedron with four shorter Cu(II)&O bonds and two longer in axial position. The equatorial bond lengths were found to be 1.89–1.91 ± 0.02 Å and the axial 2.20–2.24 ± 0.02 Å with no effect of the Jahn-Teller distortion of the octahedron when the glass composition was altered.
CRIS-Team Scopus Importer:2023-04-20
Keywords: EXAFS; Ligand field theory; Mixed alkali; UV–Vis-NIR; XANES and Jahn-Teller distortion